A REVIEW ON CLINICAL EXAMINATION OF AGNIBALA (DIGESTIVE POWER) - Rupashri, Nath; Bidhan, Mahajon; Apala, Sengupta; Abichal, Chaterjee; Remadevi, R. (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda, the science of life mainly deals with the preventive aspect of diseases along with curative aspect and this is the aim of Ayurveda. For that prevention purpose life style modification is very much essential now a day. Some factors are responsible for the formation of a disease among of them Agni is one of the most important factor. Agni plays an important role to sustain the life process. All the diseases are caused due to impaired function of Agni. According to modern science, Gastric juice and enzymes functioning at gastro intestinal level, all are responsible for digestion, absorption and metabolism. Altered function of the enzymes secreted from gastro intestinal tract is responsible for production of gastro intestinal diseases. Function of Agni is likely to be compared with gastric juice and different enzymes at gastro intestinal level. In the present era, the diseases related to Annavaha srota and Purishvaha srota (Gastro intestinal system) are commonly found in clinical practice. In the pathogenesis of disease, Dosha, Dusya, Srota, Agni and Ama (Prime causative factors of diseases) are required to be analyzed for fruitful treatment. In present study center of attention has given on clinically evaluation of Agnibala (Digestive power) based on Ancient classical theory.